Interview zur Drogenpolitik - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2016)
Dieser Artikel dokumentiert ein Interview zur Drogenpolitik. Erläutert werden die innen- und außenpolitischen Folgen der Prohibitionspolitik. Im Zentrum steht das Argument, dass Schwarzmärkte keinen Verbraucherschutz gewährleisten. – – This article documents an interview on the politics of drug prohibition. It explains the consequences of prohibiting drugs both for internal and external politics. The crucial argument is that black markets do not provide consumer protection.
urn:nbn:de:gbv:3:2-54063
Keywords: 330; Drogenpolitik; Prohibition; Schwarzmarkt; Verbraucherschutz; Leistungswettbewerb; drug policy; prohibition; black markets; consumer protection; functional competition